Measurement of B0s and D−s meson lifetimes - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
We report on a measurement of the flavor-specific B0s lifetime and of the D−s lifetime using proton-proton collisions at center-of-mass energies of 7 and 8 TeV, collected by the LHCb experiment and corresponding to 3.0 fb−1 of integrated luminosity. Approximately 407 000 B0s→D(*)−sμ+νμ decays are partially reconstructed in the K+K−π−μ+ final state. The B0s and D−s natural widths are determined using, as a reference, kinematically similar B0→D(*)−μ+νμ decays reconstructed in the same final state. The resulting differences between widths of B0s and B0 mesons and of D−s and D− mesons are ΔΓ(B)=−0.0115±0.0053(stat)±0.0041(syst) ps−1 and ΔΓ(D)=1.0131±0.0117(stat)±0.0065(syst) ps−1, respectively. Combined with the known B0 and D− lifetimes, these yield the flavor-specific B0s lifetime, τfsB0s=1.547±0.013(stat)±0.010(syst)±0.004(τB) ps and the D−s lifetime, τD−s=0.5064±0.0030(stat)±0.0017(syst)±0.0017(τD) ps. The last uncertainties originate from the limited knowledge of the B0 and D− lifetimes. The results improve upon current determinations.